EHT0202 in Alzheimer's Disease: A 3-Month, Randomized, Placebo- Controlled, Double-Blind Study - Vellas, B.; Sol, O.; J. Snyder, P.; Ousset, P.-J.; Haddad, R.; Maurin, M.; Lemarie, J.-C.; Desire, L.; P. Pando, M. (Current Alzheimer Research, 2011)
Background: EHT0202 (etazolate hydrochloride) is a new compound exhibiting both potential diseasemodifying and symptomatic treatment properties in Alzheimer's Disease increasing alpha-secretase activity and sAPP alpha secretion, as well as acting as a GABA-A receptor modulator and as a PDE-4 inhibitor. Methods: This pilot, randomized, double-blind, placebo-controlled, parallel group, multicentre, Phase IIA study was conducted in 159 randomized patients suffering from mild to moderate Alzheimer's Disease. EHT0202 (40 or 80mg bid) or placebo was administered as adjunctive therapy to one acetylcholinesterase inhibitor over a 3-month period. This study was designed to assess the clinical safety and tolerability of EHT0202 as a primary objective, with secondary endpoints (cognitive function, daily living activities, behaviour, caregiver burden and global functioning) included to explore clinical efficacy of EHT0202 versus placebo. Results: EHT0202 was shown to be safe and generally well tolerated. Dose-dependent numbers of early withdrawal and central nervous system related adverse events were observed. As expected, since the study was not powered and not designed to show drug efficacy, and except for ratings on the ADCS-ADL scale, no significant differences were seen between treatment groups. Conclusions: These first encouraging safety results do support further development of EHT0202 in order to assess its clinical efficacy and to confirm its tolerability in a larger cohort of Alzheimer patients and for a longer period.
Keywords: clinical trials randomized controlled